2015
DOI: 10.1097/eja.0000000000000246
|View full text |Cite
|
Sign up to set email alerts
|

A pharmacodynamic evaluation of dexmedetomidine as an additive drug to ropivacaine for peripheral nerve blockade

Abstract: Dexmedetomidine mixed with ropivacaine produces a dose-dependent prolongation of sensory block and clinically relevant dose-dependent sedation. Dexmedetomidine 100 μg may represent a balance between efficacy and sedation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 27 publications
2
51
0
1
Order By: Relevance
“…Two previous trials in healthy volunteers investigated ulnar nerve blocks and found a mean (SD) duration of 350 (54) min when using ropivacaine alone2 and 546 (198) min when adding 100 µg dexmedetomidine to ropivacaine 4. We have previously found that the duration of a saphenous nerve block with systemic dexmedetomidine was 10% shorter than a block with perineural dexmedetomidine using a similar protocol as the current trial 5.…”
Section: Methodssupporting
confidence: 54%
See 2 more Smart Citations
“…Two previous trials in healthy volunteers investigated ulnar nerve blocks and found a mean (SD) duration of 350 (54) min when using ropivacaine alone2 and 546 (198) min when adding 100 µg dexmedetomidine to ropivacaine 4. We have previously found that the duration of a saphenous nerve block with systemic dexmedetomidine was 10% shorter than a block with perineural dexmedetomidine using a similar protocol as the current trial 5.…”
Section: Methodssupporting
confidence: 54%
“…As bilateral surgery is rare, we conducted the trial in healthy volunteers, and it is uncertain how these results will transfer to clinical practice. Although 100 µg of dexmedetomidine seems optimal for prolonging nerve blocks,4 we observed sedative and hemodynamic side effects that may limit the clinical usefulness in such a high dose, including ambulatory settings. A subgroup analysis from a recent systematic review suggested that a lower dose of dexmedetomidine of 50–60 µg maximized block prolongation while minimizing hemodynamic side-effects 1.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…assessed the dose dependency of dexmedetomidine when added to ropivacaine for peripheral nerve blockade. [14] In their study, all volunteers received an ulnar nerve block with 22.5 mg ropivacaine alone (R), or mixed with 50 (RD50), 100 (RD100) or 150μg (RD150) dexmedetomidine. There was a significant dose-dependent increase in the mean duration (SD) of analgesia with dexmedetomidine: R: 8.7 h, RD50: 16.4 h, RD100: 20.4 h and group RD150: 21.2 h. Sedation was also enhanced in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] We had used clonidine and dexmedetomidine in a safe allowable doses to get maximum benefit. Keplinger et al studied different doses of dexmedetomidine with local anesthetics for peripheral nerve block, and found significant dose-dependent increase in the mean duration of analgesia [9] and Singelyn et al reported that a minimum dose of clonidine (0.5 µg/kg) added to mepivacaine prolongs the duration of anesthesia and analgesia in brachial plexus block. No added benefits were found with doses exceeding 1.5 µg/kg.…”
Section: Discussionmentioning
confidence: 99%